Dementia and its Relations Between the Late 20th and 21st Century - Feo, Gian Marco Di; Emond, Michael; Ghassemkhani, Kassra (Advances in Social Sciences Research Journal, 2023)
This study was conducted to examine changes in the beliefs and contents of articles on dementia from the 20th century. Factors analyzed included the form of dementia, pharmaceutical drugs, source country and income of the first author, diagnostics, and the year of publication. All articles (N=202) analyzed were published between January 1st, 1984, and December 31st, 2022. Inter-rater reliability was assessed and there was an 89.4 percent agreement amongst raters. All articles were analyzed through both PubMed and PsycInfo. Our results proved that a significant number of articles discussed Alzheimer’s disease. Scientific perspectives on the cause of dementia have not changed significantly between the 20th and 21st century. Additionally, there were no significant differences between high-, middle- and low-income countries discussing pharmaceutical drugs in literature.